Various Portrayals of Drugs and Drug Abuse in Turkish Cinema: A Sociological Analysis of Drug-related Turkish Movies - (:unkn) unknown (TURKISH GREEN CRESCENT SOC, 2021)
This study aimed to analyze the portrayals of drugs and drug abuse in Turkish movies within a sociological context. Considering the mutual relationship between cinema and society, the question of whether drugs and drug abuse have been represented in these movies in a problem-based manner constitutes the main problematic of this study, which aims to analyze a variety of drug-related films. Therefore, 54 Turkish movies including the element of drugs have been chosen in a purposive sampling and they have been analyzed by using sociological film analysis as a research technique. Of the 54 movies in the sampling, only 27 depicted drug abuse and only 24 of them portrayed negative outcomes of drug abuse. Findings supporting a positive correlation between the drug abuse portrayals and the periodical popularity of these substances have been achieved. Emphasizing the reasons behind drug abuse and addiction, the neglect in dysfunctional families and the influence of the social environment have been stressed in various movies, whereas the solutions, preventive measures, and social messages displayed in the movies remain at low numbers. The promotion of the realistic representations of drug abuse in cinema in order to raise public awareness has been recommended.
Keywords: Drug abuse; drug addiction; drugs; film; portrayal; sociological film analysis; Turkish cinema